Association between Depression, Nutritional Status, and Inflammatory Markers in Peritoneal Dialysis Patients. (February 2013) - Cilan, Havva; Sipahioglu, Murat Hayri; Oguzhan, Nilüfer; Unal, Aydin; Turan, Tayfun; Koc, Ayse Nedret; Tokgoz, Bulent; Utas, Cengiz; Oymak, Oktay
<x xml:space="preserve">Abstract</x> Background: To investigate the relationship between depression, nutritional status, and inflammatory markers in patients on peritoneal dialysis (PD). Patients and Methods: This prospective study included 40 PD patients and 20 healthy people. The severity of depressive symptoms was assessed using the Beck Depression Inventory, the Hamilton Depression Rating Scale, and the Hamilton Anxiety Rating Scale. The depressive patients received antidepressant drug for 8 weeks. Blood samples were taken before and after antidepressant treatment for the high-sensitive C-reactive protein (hs-CRP), interleukin (IL)-1, IL-6, and tumor necrosis factor-α (TNF-α) levels. Results: Ten (25%) of the 40 PD patients had depression. No significant difference was determined between depressive patients and nondepressive patients. The mean erythrocyte sedimentation rate was higher in depressive patients. There was no significant difference for other inflammation parameters, including hs-CRP, TNF-α, IL-1, and IL-6, between depressive patients and nondepressive patients. In the depressive patients, we did not observe any significant change in nutritional parameters after antidepressant treatment. When we evaluated inflammation parameters of the depressive patients before and after antidepressant treatment, only IL-1 and IL-6 levels were significantly increased after antidepressant treatment. Conclusion: The depressive disorder in PD patients is a common psychopathology and has no significant effects on nutritional status and inflammation.